Tingkat Kecemasan dengan Lama Rawat Inap Covid 19: The Level of Anxiety and Length of Hospitalization in Covid-19 Patients - Retno Wulandari; Aisyah Safitri; Sri Mintasih (Journal of Nursing Education and Practice, 2021)
Introduction: The patient's level of anxiety while undergoing treatment at the hospital greatly affects the length of stay in the hospital. Purpose: The purpose of this study was to determine the relationship between the anxiety level of COVID-19 patients and the length of patient care in the COVID-19 inpatient room at the Kalideres Hospital, Jakarta in 2021. Methods: This type of quantitative research is correlative with a cross sectional approach. The population in this study were covid 19 patients in the inpatient room for covid 19 patients at Kalideres Hospital, Jakarta in 2021 and the sample needed in this study was 54 respondents with the accidental sampling method. The researcher's data analysis used the Spearman-Ro Rank test. Results: Based on the results of the study, the description of the level of anxiety of most of the patients' anxiety was severe anxiety, as many as 26 respondents (48.1%). The description of the length of treatment partly is long, as many as 38 respondents (70.4%). The results of statistical tests are known with the value of P = 0.000 <0.05. Conclusion: There is a relationship between the anxiety level of COVID-19 patients and the length of patient care in the inpatient room at the Kalideres Hospital in 2021